Portrait of Mathematical Anxiety in Early Youth Ages - Rosyita Anindyarini; Supahar Supahar (International Journal of Trends in Mathematics Education Research, 2019)
Mathematical anxiety is considered as one of the psychological obstacles that shall be considered by every mathematics teacher. Symptoms that felt by students are in various forms. This can also influence the student’s interests and learning outcomes of mathematics. But in fact, teachers are  giveless attention to this problem so students tend to learn with less supported conditions and situations. This study aims to describe the level of mathematical anxiety and the forms of symptoms of mathematical anxiety that occur in early adolescents, and their influence on learning interest by gender consideration. The quantitative approach with the survey design of 404 students in junior high schools spread across Central Java and Yogyakarta Special Province was used in this study. Anxiety test instruments were used to collect premier data and  interviews were used as supporting data. The results of the study showed that the mathematics anxiety level of the teenage as follows: Forget about mathematic lesson, more frekwntly breathing, having a thinking disorder such as difficulty concentrating and more afraid toface math test than other subjects The findings also show that gender influences mathematical anxiety, but mathematics anxiety does not significantly affect in learning interest.